2016
DOI: 10.1590/1806-9282.62.01.85
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral aneurysms associated with human immunodeficiency virus in adults: literature review and new perspectives

Abstract: SUMMARY Introduction: the treatment of human immunodeficiency virus (HIV) infection has been decreasing patient morbidity and mortality by opportunistic infections and, thus, survival has increased. This new reality has been changing the spectrum of diseases affecting such patients. Objective: to discuss the association between HIV and the emergence of aneurysmal brain injuries. Method: it was performed a literature review using medical database. The following descriptors were searched: "Intracranial Aneury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
6
0
2
Order By: Relevance
“…This finding is compatible with previous reports [21][22][23]. In those reports, chronic inflammation caused by HIV itself or by opportunistic infections was thought to be responsible for vulnerabilities of blood vessels and related to the formation of cerebral aneurysms.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is compatible with previous reports [21][22][23]. In those reports, chronic inflammation caused by HIV itself or by opportunistic infections was thought to be responsible for vulnerabilities of blood vessels and related to the formation of cerebral aneurysms.…”
Section: Discussionsupporting
confidence: 93%
“…The actual incidence may be underestimated because patients are asymptomatic in many cases (5). Aneurysmal vasculopathy associated with HIV infection is usually related to fusiform dilatation and occurs in young adults (6). According to a recent systematic review of HIV-associated cerebral aneurysmal vasculopathy cases (16 adults) reported in the literature, the commonly affected arteries were middle cerebral artery (68.8%) followed by the anterior cerebral artery (62.5%) in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Опубликованные единичные клинические на-блюдения [63][64][65][66][67] однотипны. Как правило, больных госпитализировали в отделение неотложной помощи с острой неврологической симптоматикой.…”
Section: геморрагические нарушенияunclassified